Experimental investigation of vortex structure in the corrugated channel - (:unkn) unknown (American Society of Mechanical Engineers (ASME), 2013)
Vortex structure in a corrugated channel has been studied with a PIV system measuring two-dimensional velocity fields at different locations and Reynolds numbers. The geometry of corrugation under investigation is the two-dimensional reflection of the circular cross-sectional stainless-steel flex pipe. The results show that turbulence caused by the corrugated wall affects the whole flow field in the channel even at low Reynolds number. The bulk flow field is rather chaotic in the entire channel. Moreover, the velocity vectors show significant interaction between the flow in the groove and the bulk flow. Vortex generated from the groove is very unstable and intermittent, and the vortex is not confined within the groove even at low Reynolds number. Vortex in the groove either migrates out of the groove without breaking up, or causes bursting flow from the groove to the bulk. In addition, intermittent and time-mean flow reversals are observed near the crest of the corrugation at low Reynolds number. Though the channel design is intended to be two-dimensional, flow structures in the groove appear to be three-dimensional at high Reynolds number while two-dimensional at low Reynolds number. Copyright © 2013 by ASME.